2011
DOI: 10.19030/cier.v1i3.1193
|View full text |Cite
|
Sign up to set email alerts
|

Expanding Marketing Principles For The Sale Of Higher Education

Abstract: This paper will develop and explain a conceptual framework for the use of business industry marketing techniques within the higher educational spectrum. This framework will demonstrate how sound marketing management can help higher education increase its effectiveness and improve student interest, as well as encourage the development of managerial skills that will lead to better operational efficiency.  The material will be presented in a detailed, specific, and practical manner that can be utilized by educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Consistent with previous research, sacrifice is conceptualized as what the customer sacrifices in order to receive a service (Cronin, Brady and Hult, 2000). Rudd and Mills (2008) identified that high prices set by universities limit the number of potential possible students who could afford these courses. Not limited to money, other sacrifices such as time and effort are components of sacrifice (Cronin et al, 1997).…”
Section: Sacrifice and Service Valuementioning
confidence: 77%
See 2 more Smart Citations
“…Consistent with previous research, sacrifice is conceptualized as what the customer sacrifices in order to receive a service (Cronin, Brady and Hult, 2000). Rudd and Mills (2008) identified that high prices set by universities limit the number of potential possible students who could afford these courses. Not limited to money, other sacrifices such as time and effort are components of sacrifice (Cronin et al, 1997).…”
Section: Sacrifice and Service Valuementioning
confidence: 77%
“…These motivations stemmed from the fact that most of the student sample felt that the fees were too high; thus exemplifying that overpricing can have dire consequences. According to Rudd and Mills (2008), charging too high a price can drain the pool of too many prospective students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation